2009
DOI: 10.1001/archinternmed.2008.587
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Costs in the Last Week of Life

Abstract: Background Life-sustaining medical care of cancer patients at the end-of-life (EOL) is costly. Patient-physician discussions about EOL wishes were found to be associated with lower rates of intensive interventions. Methods Coping with Cancer (CwC) is an NCI/NIMH-funded, longitudinal, multi-institutional study of 627 advanced cancer patients. Patients were interviewed at baseline and followed through death. Costs for ICU/hospital stays, hospice care and life-sustaining procedures (e.g., ventilation, resuscita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
258
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 795 publications
(271 citation statements)
references
References 20 publications
(22 reference statements)
9
258
1
3
Order By: Relevance
“…4,137 Some studies have reported benefits. 128,[130][131][132]138,139 These tend to be based on surveys, and to focus on a comparative reduction in days and deaths in hospital and costs associated with care in the last year of life. Detering et al 128 report the results of a randomised controlled trial in Australia in which patients receiving a structured ACP intervention were more likely to die in their preferred place.…”
Section: 114mentioning
confidence: 99%
See 1 more Smart Citation
“…4,137 Some studies have reported benefits. 128,[130][131][132]138,139 These tend to be based on surveys, and to focus on a comparative reduction in days and deaths in hospital and costs associated with care in the last year of life. Detering et al 128 report the results of a randomised controlled trial in Australia in which patients receiving a structured ACP intervention were more likely to die in their preferred place.…”
Section: 114mentioning
confidence: 99%
“…ACP is reported to increase the chances of patients dying in their preferred place, assumed usually to be home, and experiencing less invasive (and less costly) treatment. 128,[130][131][132]138,139 Nevertheless, evidence regarding the effectiveness of ACP is limited and conflicting. 4 The policy is not based on evidence about patients' and the public's understanding and experience of ACP, their preferences for how and when this should be discussed, or their attitudes to death and dying.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 25% of beds in 69 intensive care units (ICUs) were occupied by patients whom attending intensivists perceived as receiving inappropriate care. 62 A more conservative or palliative approach to end-of-life care has been shown, in the case of patients with advanced cancer, to prolong survival, improve symptoms, avoid invasive care, reduce hospital stays and lower costs (by up to one-third 63 ) compared with more aggressive care. 64 Similar outcomes are possible if advance care planning was systematically applied to patients with end-stage chronic diseases.…”
Section: Adopt a More Conservative Approach Nearing The End Of Lifementioning
confidence: 99%
“…ACP helps patients to: (a) reflect on their goals, beliefs, and values; (b) consider future medical treatment preferences; (c) appoint and prepare a surrogate decision-maker; and (d) document their wishes regarding future medical treatment [3] . There are a number of favorable outcomes associated with ACP, including: increased satisfaction with care; improved patient quality of life in terminal illness; and better psychological outcomes for family members after patient death [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…PHRs also aid individuals in taking a more active role in health management and decision-making [5] . PHRs make up-to-date, personal health information accessible to patients.…”
Section: Introductionmentioning
confidence: 99%